2020
DOI: 10.1111/pim.12728
|View full text |Cite
|
Sign up to set email alerts
|

Immune serum–activated human macrophages coordinate with eosinophils to immobilize Ascaris suum larvae

Abstract: Shaping the future of infectious diseases treatments.Author contributions: GC analysed and plotted data and wrote the manuscript, BV, TB and KS designed and performed experiments, AB analysed RNA seq data, PG provided reagents and larvae, MH and WGCH provided human serum samples, JEvB and NLH designed and supervised the study and sought funding. NLH contributed to writing the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…Moreover, using the same methodology, anti-Ascaris IgG 4 seropositive serum has been shown to react with live larvae. 58 Both strategies strengthen our findings and suggest that we are truly measuring antibodies toward Ascaris. Exposure to Anisakis simplex due to fish consumption could be a potential cause of cross-reactivity; however, a study of Norwegian blood donors showed a prevalence of almost 0 for IgE sensitization toward Anisakis.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, using the same methodology, anti-Ascaris IgG 4 seropositive serum has been shown to react with live larvae. 58 Both strategies strengthen our findings and suggest that we are truly measuring antibodies toward Ascaris. Exposure to Anisakis simplex due to fish consumption could be a potential cause of cross-reactivity; however, a study of Norwegian blood donors showed a prevalence of almost 0 for IgE sensitization toward Anisakis.…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, Arg1-mediated trapping of N. brasiliensis larvae by macrophages required the IgE/ FceR-driven activation of IL-4producing basophils [4]. Recently, an important role for antibody-activated macrophages in larval trapping has also been shown for the human parasite Ascaris lumbricoides [6]. However, in contrast to macrophage-mediated immunity to the rodent parasite H. polygyrus, antibodymediated trapping of Ascaris larvae was greatly enhanced in the presence of eosinophils, which were recruited by immune serum-activated human macrophages [2,6].…”
Section: Antibody-mediated Macrophage Functions In Host Defense and R...mentioning
confidence: 99%
“…However, based on their exceptional plasticity, macrophages have evolved multiple strategies to efficiently combat helminth parasites and to limit parasite-induced tissue damage (Figure 1). Macrophage-mediated host defense against helminth parasites largely relies on the activation of an alternatively activated macrophage (AAM) phenotype, which can trap and/ or kill helminth larvae or stimulate the expulsion of adult parasites [2][3][4][5][6][7]. While AAM-mediated helminth trapping prevents extensive injury of infected tissues [2,8], AAM also actively contribute to tissue repair by producing growth factors, chemokines and building blocks for collagen synthesis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…eosinophil, Giardia muris, IgA, ILC3, parasite, protozoa, Th17 nematodes. 9,11,12 However, the healthy small intestine harbours high numbers of eosinophils, which support Peyer's patches (PP) development and mucus production 13 and promote homeostatic IgA antibody class switching (CS). Eosinophils also support IgAproducing plasma cells in the small intestinal lamina propria (siLP) at steady state, and during intestinal nematode and Toxoplasma gondii infection.…”
Section: Introductionmentioning
confidence: 99%